POLITIK UMAT ISLAM INDONESIA: UPAYA DEPOLITISASI PASCAKEMERDEKAAN - Mutawakkil, Mutawakkil (Hunafa: Jurnal Studia Islamika, 2009)
This paper deals with political relations between the state and Moslem communities in Indonesia at the first emergence until being political power from the seventh century to the beginning of the nineteenth century. This issue will be discussed using socio-historical analysis. Based on the data analysis, the Muslim community played a significant role in a parliamentary democracy. Thus, they were marginalized in a guided democracy, and become an object, rather than a subject, both in the New Order and the Reform era, in terms of a variety of national issues. In other words, Muslim community become a target of depolitization and such issues as the sole principle, moral education of Pancasila, veiling, right-wing extremists, and terrorism, despite of the fact that the 1945 Constitution gives to all Indonesian people a freedom to embrace their religion.Kata Kunci: politik Islam, depolitisai, umat Islam Indonesia